Central Cell in Flowering Plants: Specification, Signaling, and Evolution - Li, Hong-Ju; Yang, Wei-Cai (Frontiers in Plant Science, 2020)
During reproduction of animals and lower plants, one sperm cell usually outcompetes the rivals to fertilize a single egg cell. But in flowering plants, two sperm cells fertilize the two adjacent dimorphic female gametes, the egg and central cell, respectively, to initiate the embryo and endosperm within a seed. The endosperm nourishes the embryo development and is also the major source of nutrition in cereal for human beings. Central cell as one of the key innovations of flowering plants is the biggest cell in the multicellular haploid female gametophyte (embryo sac). The embryo sac is the product of successive events of nuclear divisions, cellularization, and cell specification of the meiosis-generated megagametophyte. Nowadays, accumulating lines of evidence are raveling multiple roles of the central cell rather than only the endosperm precursor. In this review, we summarize the current understanding of its cell fate specification, intercellular communication with other gametophytic cells, and evolution. We also highlight some key unsolved questions for the further studies in this field.